PENGARUH KEBIJAKAN UTANG DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN KEUANGAN SUBSEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2019-2023 - Fadillah, Pratiwi; Nasution, Ilham Ramadhan (UNIVERSITAS DHARMAWANGSA, 2025)
The decline and fluctuation in the value of banking sector companies listed on the Indonesia Stock Exchange (IDX) highlight the need for effective financial management, particularly through debt policy and dividend policy. This study aims to analyze the influence of debt policy and dividend policy on the firm value of banking companies listed on the IDX during the 2019–2023 period. A quantitative approach was employed in this study, utilizing multiple linear regression analysis. The sample consisted of 11 banking companies, totaling 55 annual observations, selected through purposive sampling based on specific criteria. The independent variables in this research are debt policy, measured by the Debt to Equity Ratio (DER), and dividend policy, measured by the Dividend Payout Ratio (DPR), while firm value is measured by the Price to Book Value (PBV). The results indicate that debt policy and dividend policy each have a significant partial effect on firm value. Furthermore, both variables simultaneously have a positive and significant effect on firm value. These findings imply that banking companies need to optimize their capital structure and dividend distribution strategies to enhance investor confidence and improve firm value in the market.